“Drinkers Like Me”: A Thematic Analysis of Comments Responding to an Online Article About Moderating Alcohol Consumption - Irizar, Patricia; Puddephatt, Jo-Anne; Warren, Jasmine G.; Field, Matt; Jones, Andrew; Rose, Abigail K.; Gage, Suzanne H.; Goodwin, Laura (Frontiers in Psychology, 2022)
Background There has been media coverage surrounding the dangers of heavy drinking and benefits of moderation, with TV and radio presenter, Adrian Chiles, documenting his experience of moderating alcohol consumption in an online article for the Guardian. By analysing the comments in response to Chiles’ article, this study aimed to explore (i) posters’ (someone who has posted a comment in response to the article) attitudes or beliefs toward moderating alcohol and (ii) posters’ experiences of moderating or abstaining from alcohol. Method A secondary qualitative analysis of online comments in response to an article about moderating alcohol consumption. Main outcome measures: Comments (n = 784) in response to a United Kingdom online news article about moderating alcohol consumption were extracted and inductive thematic analysis was used. Results For aim one, two themes were developed; “general attitudes toward drinking” and “general attitudes toward reducing consumption”. These themes reflect negative perceptions of alcohol and issues around changing attitudes. For aim two, three themes were developed: “moderation vs. abstention”, “reflection on past drinking behaviours”, and “current drinking behaviours”. These themes represent posters’ experiences and implications changing their drinking habits. Conclusion Our analysis provides a novel insight into perceptions and experiences of moderating or abstaining from alcohol. Alcohol is embedded within United Kingdom culture, creating difficulties for those who choose to moderate or abstain from alcohol. Our analysis highlights the need for public health to focus on shifting the current drinking culture, through clearer drinking guidelines and a wider availability of alcohol-free alternatives.